Hidden Polynomial! (No easy logic)

Algebra Level 2

{ a + b + c = 3 a 2 + b 2 + c 2 = 5 a 3 + b 3 + c 3 = 7 \large \begin{cases}{a+b+c=3} \\ {a^2 +b^2 +c^2 =5} \\ {a^3 + b^3 +c^3 = 7} \end{cases}

If a , b , c a,b,c are complex numbers satisfying the system of equations above, find the value of a 4 + b 4 + c 4 a^4 + b^4 + c^4 .

Note: I found the problem in my Book. See: "Ayo Raih Medali Emas Olimpiade Matematika" (English: Let's Get A Gold Medal in Mathematics Olympiad) by: Dr. Khow Yao Tung, M. Sc. Ed, MEd.


The answer is 9.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

5 solutions

Figel Ilham
May 26, 2015

Let's we make the monic polynomial with degree 3, rewrite x 3 + A x 2 + B x + C x^3+ Ax^2 +Bx+C and let a , b , c a,b,c roots of the polynomial, then according to Newton's Sums with P k = a k + b k + c k P_k = a^k + b^k + c^k , then we have P 1 + A = 0 P_1 + A = 0 3 + A = 0 A = 3 3+A=0 \Rightarrow A = -3 P 2 + A P 1 + 2 B = 0 P_2 + AP_1+2B = 0 5 + ( 3 ) 3 + 2 B = 0 B = 2 5+(-3)3+2B=0 \Rightarrow B = 2 P 3 + A P 2 + B P 1 + 3 C = 0 P_3+AP_2+BP_1+3C = 0 7 + ( 3 ) 5 + 2 ( 3 ) + 3 C = 0 C = 2 3 7+(-3)5+2(3)+3C=0 \Rightarrow C = \frac{2}{3} P 4 + A P 3 + B P 2 + C P 1 = 0 P_4+AP_3+BP_2+CP_1 = 0 P 4 + ( 3 ) 7 + 2 ( 5 ) + 2 3 ( 3 ) = 0 P 4 = 9 P_4+(-3)7 +2(5)+\frac{2}{3}(3) = 0 \Rightarrow P_4 = 9

Note: using algebraic manipulation is extremely tedious!

Moderator note:

Good. Bonus question: Is it true that a 5 + b 5 + c 5 = 11 a^5 + b^5 + c^5 = 11 ?

For Challenge Master note, it is absolutely INCORRECT. Using Newton's Sum, we have P 5 3 P 4 + 2 P 3 + 2 3 P 2 = 0 P_5 -3P_4 +2P_3+\frac{2}{3}P_2 = 0 The P 2 = 5 P_2 = 5 , since 2 3 × 5 \frac{2}{3}\times 5 is a fraction, absolutely the answer must be in fraction. Thus, observation is extremely a complete mistake! The result of P 5 = 29 3 P_5 = \frac{29}{3}

Thanks to Master @Pi Han Goh

Figel Ilham - 6 years ago

Log in to reply

It's 29 3 \frac{29}3 , not 49 3 \frac{49}{3} . EDIT: Haha, don't call me master~!

Pi Han Goh - 6 years ago

Log in to reply

Sorry, miscounted. Edited

Figel Ilham - 6 years ago

why is this question given in complex numbers search it should be there in vieta's .There is no trace of complex numbers in the solution.

Raven Herd - 3 years, 9 months ago

A good solution by Figel Ilham.

Mahavishnu Brandao - 6 years ago
Sujit Debnath
May 27, 2015

Given that, a + b + c a + b + c = 3, a 2 + b 2 + c 2 a^2 + b^2 + c^2 = 5, a 3 + b 3 + c 3 a^3 + b^3 + c^3 = 7

We know that,
formula-1: a 2 + b 2 + c 2 a^2 + b^2 + c^2 = ( a + b + c ) 2 (a + b + c)^2 - 2 ( a b + b c + c a ) 2(ab + bc + ca)
formula-2: a 3 + b 3 + c 3 3 a b c a^3 + b^3 + c^3 - 3abc = ( a + b + c ) ( a 2 + b 2 + c 2 a b b c c a ) (a + b + c) (a^2 + b^2 + c^2 - ab - bc - ca)

Using formula-1, ab + bc + ca = 3 2 5 2 \frac {3^2 - 5}{2} = 2
Using formula-2, abc = 2 3 - \frac {2}{3}

From formula-1, we can write that,
( a b ) 2 + ( b c ) 2 + ( c a ) 2 (ab)^2 + (bc)^2 + (ca)^2
= ( a b + b c + c a ) 2 2 ( a b × b c + b c × c a + c a × a b ) (ab + bc + ca)^2 - 2(ab \times bc + bc \times ca + ca \times ab)
= ( a b + b c + c a ) 2 2 a b c ( a + b + c ) (ab + bc + ca)^2 - 2abc(a + b + c)
= 2 2 2 × ( 2 3 ) × 3 2^2 - 2 \times (- \frac {2}{3}) \times 3 = 8

So, a 4 + b 4 + c 4 a^4 + b^4 + c^4
= ( a 2 ) 2 + ( b 2 ) 2 + ( c 2 ) 2 (a^2)^2 + (b^2)^2 + (c^2)^2
= ( a 2 + b 2 + c 2 ) 2 2 [ ( a b ) 2 + ( b c ) 2 + ( c a ) 2 ] (a^2 + b^2 + c^2)^2 - 2[(ab)^2 + (bc)^2 + (ca)^2]
= 5 2 2 × 8 5^2 - 2 \times 8 = 9

Moderator note:

Yes, Newton's Identities is more than enough to solve this problem. Bonus question: Can you prove that a 5 + b 5 + c 5 = 29 3 a^5 + b^5 + c^5 = \frac{29}3 with just Newton's Identities alone?

Good ones!

Figel Ilham - 6 years ago

Good job :-)

Mehedi Hasan - 6 years ago

Prove of bonus question,
( a 2 + b 2 + c 2 ) ( a 3 + b 3 + c 3 ) (a^2 + b^2 + c^2)(a^3 + b^3 + c^3) = 5 × 7 5 \times 7
a 5 + a 2 b 3 + c 3 a 2 + a 3 b 2 + b 5 + b 2 c 3 + c 2 a 3 + b 3 c 2 + c 5 \Rightarrow a^5 + a^2b^3 + c^3a^2 + a^3b^2 + b^5 + b^2c^3 + c^2a^3 + b^3c^2 + c^5 = 35
a 5 + b 5 + c 5 + a 3 b 2 + a 2 b 3 + b 3 c 2 + b 2 c 3 + c 3 a 2 + c 2 a 3 \Rightarrow a^5 + b^5 + c^5 + a^3b^2 + a^2b^3 + b^3c^2 + b^2c^3 + c^3a^2 + c^2a^3 = 35
a 5 + b 5 + c 5 + a 2 b 2 ( a + b ) + b 2 c 2 ( b + c ) + c 2 a 2 ( c + a ) \Rightarrow a^5 + b^5 + c^5 + a^2b^2(a + b) + b^2c^2(b + c) + c^2a^2(c + a) = 35
a 5 + b 5 + c 5 + a 2 b 2 ( 3 c ) + b 2 c 2 ( 3 a ) + c 2 a 2 ( 3 b ) \Rightarrow a^5 + b^5 + c^5 + a^2b^2(3 - c) + b^2c^2(3 - a) + c^2a^2(3 - b) = 35
a 5 + b 5 + c 5 + 3 a 2 b 2 a 2 b 2 c + 3 b 2 c 2 a b 2 c 2 + 3 c 2 a 2 a 2 b c 2 \Rightarrow a^5 + b^5 + c^5 + 3a^2b^2 - a^2b^2c + 3b^2c^2 - ab^2c^2 + 3c^2a^2 - a^2bc^2 = 35
a 5 + b 5 + c 5 + 3 [ ( a b ) 2 + ( b c ) 2 + ( c a ) 2 ] a b c ( a b + b c + c a ) \Rightarrow a^5 + b^5 + c^5 + 3[(ab)^2 + (bc)^2 + (ca)^2] - abc(ab + bc + ca) = 35
a 5 + b 5 + c 5 + 3 × 8 ( 2 3 ) × 2 \Rightarrow a^5 + b^5 + c^5 + 3 \times 8 - (- \frac {2}{3}) \times 2 = 35
So, a 5 + b 5 + c 5 a^5 + b^5 + c^5 = 29 3 \frac {29}{3}

Sujit Debnath - 6 years ago
Rajen Kapur
Jun 2, 2015

I offer appreciation for the Note in the question, as it reveals the beauty of Indonesian language.

What makes so special :) ?

Figel Ilham - 6 years ago

each and every step increase 2 (value) ) ..so finally we get answer is 7 ![](

Moderator note:

Like Ahmed Karrany's solution, your logic is flawed. Is Figel Illham's solution.

See my solution. It's flawed

Figel Ilham - 6 years ago
Ahmed Karrany
May 26, 2015

by observation

the sum of a, b and c=3 ...........(1)

the sum of square of each a, b and c=5...........(2)

the sum of cube of each a, b and c=7 ...........(3)

the diffrence between Eqs 2 & 1 is 2

the diffrence between Eqs 3 & 2 is 2 also.

Hence

the sum of fourth order of each a, b and c=9 ...........(4)

the diffrence between Eqs 4 & 3 is 2 (constant).

Moderator note:

You're still wrong. You can't just say the pattern works because you noticed it applies for small values of n n .

If I replaced the numbers 3 , 5 , 7 3,5,7 by 1 , 2 , 3 1,2,3 respectively, do you still think that the answer will be 4 4 ? No!

Your logic is flawed. See Figel Ilham's solution.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...